1999
DOI: 10.1017/s0305000998003675
|View full text |Cite
|
Sign up to set email alerts
|

Early talk about the past revisited: affect in working-class and middle-class children's co-narrations

Abstract: This study contributes to our understanding of sociocultural variation in children's early storytelling by comparing co-narrations produced by children and their families from two European-American communities, one working-class and one middle-class. Six children from each community were observed in their homes at 2;6 and 3;0 years of age, yielding a corpus of nearly 400 naturally-occurring co-narrations of past experience. Analyses of generic properties, content, and emotion talk revealed a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 0 publications
3
54
0
Order By: Relevance
“…However, ethnographic research has suggested a rich oral tradition in many low-SES communities (Miller & Sperry 2012). Children from these communities are exposed to and engage in personal storytelling at an early age, thereby developing culture-specific narrative skills (Burger & Miller 1999, Miller et al 2005. There is evidence that children from low-SES homes engaged in more costorytelling in daily life, produced narratives of higher quality, and had better narrative comprehension than their middle-class counterparts (Burger & Miller 1999, Gardner-Neblett et al 2012).…”
Section: Narrativementioning
confidence: 99%
See 1 more Smart Citation
“…However, ethnographic research has suggested a rich oral tradition in many low-SES communities (Miller & Sperry 2012). Children from these communities are exposed to and engage in personal storytelling at an early age, thereby developing culture-specific narrative skills (Burger & Miller 1999, Miller et al 2005. There is evidence that children from low-SES homes engaged in more costorytelling in daily life, produced narratives of higher quality, and had better narrative comprehension than their middle-class counterparts (Burger & Miller 1999, Gardner-Neblett et al 2012).…”
Section: Narrativementioning
confidence: 99%
“…Children from these communities are exposed to and engage in personal storytelling at an early age, thereby developing culture-specific narrative skills (Burger & Miller 1999, Miller et al 2005. There is evidence that children from low-SES homes engaged in more costorytelling in daily life, produced narratives of higher quality, and had better narrative comprehension than their middle-class counterparts (Burger & Miller 1999, Gardner-Neblett et al 2012). Unfortunately, low-SES children's strength in narrative skills is often underestimated by teachers, because of the mismatch between home cultures and the mainstream method of instruction in schools (Dyson & Genishi 2009).…”
Section: Narrativementioning
confidence: 99%
“…In contrast to the focus on self-reliance in families from middle-class backgrounds, Miller and her colleagues (Burger & Miller, 1999;Wiley, Rose, Burger, & Miller, 1998) have suggested that European-American families from working-class backgrounds (as defined by education and occupation) focus on developing cooperation in their young children. Similarly, Guatemalan Mayan mothers with fewer years of formal schooling were more collaborative and less directive with their children than mothers with more years of formal schooling while completing a puzzle (Chavajay & Rogoff, 2002).…”
Section: Schooling and Cross-cultural Variations In Parent-child Intementioning
confidence: 99%
“…To determine whether the content in homesigned narratives is similar to that of hearing children's narratives, we applied content codes developed by Miller and Sperry [1988; see also Burger & Miller, 1999] to the deaf children's narratives. First, we coded narratives according to valence: positive if the event the narrative described had a positive valence (e.g., an enjoyable or interesting activity, such as receiving a gift, e.g., when David recounts receiving a balloon and pretzel when he went to visit Santa Claus); negative if the event it described had a negative valence (e.g., a physical injury, a scary or upsetting experience, as when the zombies in a movie frightened Qing); odd if the event it described was unusual or strange (e.g., Marvin relates that when he went bowling with his dad, there was a moose head on the wall at the bowling alley); or routine if the event it described was ordinary or habitual (e.g., Qing's mother puts coins in the fare box when they ride the bus, or David's descriptions of breathing exercises at school).…”
Section: Coding Narrative Contentmentioning
confidence: 99%